From top to bottom - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
From Messa, Cameroon, Jean Marie Hermann Ndi writes in with a question, and to explain how the content of Spore is being disseminated in his company, the SEPJMH.N. 'As soon as the new copy arrives, the management reads it thoroughly and pulls out...